Supplementary material from " Amphibalanus amphitrite begins exoskeleton mineralization within 48 hours of metamorphosis" - Metzler, Rebecca A.; O'Malley, Jessica; Herrick, Jack; Christensen, Brett; Orihuela, Beatriz; Rittschof, Daniel; Dickinson, Gary H. (The Royal Society, 2020)
Barnacles are ancient arthropods that, as adults, are surrounded by a hard, mineralized, outer shell that the organism produces for protection. While extensive research has been conducted on the glue-like cement that barnacles use to adhere to surfaces, less is known about the barnacle exoskeleton, especially the process by which the barnacle exoskeleton is formed. Here, we present data exploring the changes that occur as the barnacle cyprid undergoes metamorphosis to become a sessile juvenile with a mineralized exoskeleton. Scanning electron microscope (SEM) data show dramatic morphological changes in the barnacle exoskeleton following metamorphosis. Energy-dispersive x-ray spectroscopy (EDS) indicates a small amount of calcium (8%) 1 h post-metamorphosis that steadily increases to 28% by 2 days following metamorphosis. Raman spectroscopy indicates calcite in the exoskeleton of a barnacle 2 days following metamorphosis and no detectable calcium carbonate in exoskeletons up to 3 h post-metamorphosis. Confocal microscopy indicates during this 2-day period, barnacle base plate area and height increases rapidly (0.001 mm 2 hr −1 and 0.30 µm hr −1 , respectively). These results provide critical information into the early life stages of the barnacle, which will be important for developing an understanding of how ocean acidification might impact the calcification process of the barnacle exoskeleton.